Ga/HZSM-5 catalysed acetic acid ketonisation for upgrading of biomass pyrolysis vapours - Jahangiri, Hessam; Osatiashtiani, Amin; Ouadi, Miloud; Hornung, Andreas; Lee, Adam F.; Wilson, Karen (Catalysts, 2019)
Pyrolysis bio-oils contain significant amounts of carboxylic acids which limit their utility as biofuels. Ketonisation of carboxylic acids within biomass pyrolysis vapours is a potential route to upgrade the energy content and stability of the resulting bio-oil condensate, but requires active, selective and coke-resistant solid acid catalysts. Here we explore the vapour phase ketonisation of acetic acid over Ga-doped HZSM-5. Weak Lewis acid sites were identified as the active species responsible for acetic acid ketonisation to acetone at 350◦C and 400◦C. Turnover frequencies were proportional to Ga loading, reaching 6 min−1 at 400◦C for 10Ga/HZSM-5. Selectivity to the desired acetone product correlated with the weak:strong acid site ratio, being favoured over weak Lewis acid sites and reaching 30% for 10Ga/HZSM-5. Strong Brønsted acidity promoted competing unselective reactions and carbon laydown. 10Ga/HZSM-5 exhibited good stability for over 5 h on-stream acetic acid ketonisation.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Bio-oil; Ketonisation; Pyrolysis; Turnover frequencies (TOFs)